Genes, brain function, and behavior : what genes do, how they malfunction, and ways to repair damage - Wahlsten, D. (Academic Press, an imprint of Elsevier, 2019)
Genes, Brain Function, and Behavior offers a concise description of the nervous system that processes sensory input and initiates motor movements. It reviews how behaviors are defined and measured, and how experts decide when a behavior is perturbed and in need of treatment. Behavioral disorders that are clearly related to a defect in a specific gene are reviewed, and the challenges of understanding complex traits such as intelligence, autism and schizophrenia that involve numerous genes and environmental factors are explored. New methods of altering genes offer hope for treating or even preventing difficulties that arise in our genes. This book explains what genes are, what they do in the nervous system, and how this impacts both brain function and behavior.